Workaholism and Technostress During the COVID-19 Emergency: The Crucial Role of the Leaders on Remote Working - Spagnoli, Paola; Molino, Monica; Molinaro, Danila; Giancaspro, Maria Luisa; Manuti, Amelia; Ghislieri, Chiara (Frontiers in Psychology, 2020)
Although remote working can involve positive outcomes both for employees and organizations, in the case of the sudden and forced remote working situation that came into place during the COVID-19 crisis there have also been reports of negative aspects, one of which is technostress. In this context of crisis, leadership is crucial in sustainably managing and supporting employees, especially employees with workaholic tendencies who are more prone to developing negative work and health outcomes. However, while research on the role of the positive aspects of leadership during crises does exist, the negative aspects of leadership during the COVID-19 crisis have not yet been studied. The present study aimed to explore the role of authoritarian leadership in a sample of 339 administrative university employees who worked either completely from home or from home and the workplace. The study examined the moderating effect of a manager on this relationship and the connections between workaholism and technostress through conditional process analysis. Results pointed out that high authoritarian leadership had an enhancing effect, whereas low authoritarian leadership had a protective effect on the relationship between workaholism and technostress, only in the group of complete remote workers. Thus, authoritarian leadership should be avoided and training leaders to be aware of its effect appears to be essential. Limitations, future directions for the study, and practical implications are also discussed.